A contrastive study on invitations in English and Vietnamese / Do Van San; Supervisor: Assoc.Prof.Dr. Ho Ngoc Trung - Do, Van San
Invitations play an important role in our communication. They are used in daily life. Making a suitable invitation for each situation is not simple, especially in a foreign language. There are some researches about invitations but no research is studied on invitation strategies and forms of the invitation letters to a housewarming party, a birthday party in English and Vietnamese. This study is designed to aim at pointing out invitation strategies and forms of the invitation letters to a housewarming party, a birthday party in English and Vietnamese then finding out the similarities and differences of those features. To reach the aim, some methods are used: Descriptive method, contrastive method and analytic method. Data used for analysis, description and contrast in this study were mainly collected through existing invitations, fifty formal letters of invitation to a housewarming party, a birthday party in English and the same amount of informal letters of invitation to a housewarming party, a birthday party in Vietnamese. After having contrasted, some similarities and differences of invitation strategies and forms of the invitation letters to a housewarming party, a birthday party between English and Vietnamese have been founded. There are some implications on teaching and learning the writing theory a letter of invitation to a housewarming party, a birthday party in English as a foreign language in Nam Duyen Ha high school are carried out.